Nitric Oxide, Peroxynitrite and Malondialdehyde Levels as Markers for Nitrosative/Oxidative Stress in Iraqi Patients with Systemic Lupus Erythematosus - M. Mohammed, Shaimaa; A. Amin, Inaam; Z. Sabri, Zeina (Iraqi Journal of Pharmaceutical Sciences, 2017)
Systemic lupus Erythematosus is an autoimmune disease of unknown aetiology affecting multiple organ system. Reactive nitrogen and oxygen species are claimed to play a role in this disease. However, the potential of Nitrosative/Oxidative Stress to elicit an autoimmune, response remain till now largely unexplored in humans. This study was done to investigate the status and contribution of nitrosative/oxidative stress in Iraqi patients for systemic lupus erythematosus. Blood samples from 19 patients with systemic lupus erythematosus and 19 age-and sex- matched apparently healthy controls were evaluated for serum levels of nitrosative/oxidative stress markers including nitric oxide, peroxynitrite and malondialdehyde. Nitric oxide levels were measured by spectrophetometric method depending on Griss method, while peroxynitrite levels were measured by spectrophetometric method based on peroxynitrite mediated nitration of phenol. Malondialdehyde levels were measured by the thiobarbitoric acid method. Serum nitric oxide levels were significantly elevated in SLE patients (mean + SE 263.58 + 35.42 mmol/L) as compared with healthy control (162.48 +10.42 mmol/L). Peroxynitrite levels were also significantly elevated in a disease group (mean + SE 7.23 +0.92 mmol/L) as compared to healthy control (4.47 + 0.38 mmol/L). On the other hand, malondialdehyde levels were slightly elevated in SLE patient (mean + SE 4.53 + 0.22 nmol/ml) as compared to control group (4.32 + 0.58nmol/ml). The study findings support an association between nitrosative/oxidative stress and SLE through elevated level of NO, peroxynitrite and MDA in the serum of SLE patients. Key words: Nitric oxide, Peroxynitrite, SLE.